Equivalent weavings - Zambrano, Aliw-iw (Archīum Ateneo, 2016)
A weaving is defined as the interlacement of the overlapping simple connected graphs. In particular, weavings may be constructed from colorings of the plane. A definition of equivalent weavings constructed from colorings of the plane as well as some examples are presented in this paper.